Anak Berkonflik dengan Hukum dalam Perspektif Hukum Islam - Rina Rohayu Harun; Burhanuddin Burhanuddin (Universitas Muhammadiyah Yogyakarta, 2023)
In positive law in Indonesia related to the handling of children in conflict with the law, it focuses on legal protection for children, starting from prevention to the justice system that is in accordance with the behavior shown and carried out by children. In practice, this protection effort uses a restorative justice approach. So far, the weakness of the statutory system lies more in its implementation. For this reason, it is very interesting to study the perspective of Islamic law on cases of children in conflict with this law. At least, there is a possibility of a formulation being found to criticize or improve the system and implementation in handling positive law in Indonesia for children in conflict with the law. From the results of the discussion, it was concluded that in the teachings of Islam, providing protection to children is the duty of everyone, not only parents. When a child is in conflict with the law, he is not given legal sanctions but is delegated or charged to his parents. The child is only given ta'dibi, namely punishment that is instructive in nature and does not affect the child's psyche. The arrangement for giving ta'dibi is left to the leader or ruler.